Efek Variasi Proses Pembuatan Amazake Terhadap Kualitasnya - Khairul Anam (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2011)
Amazake is a tradisional sweet non alcoholic Japanesedrink made from fermented rice which is produced from mix of rice koji and boiled rice. In this process production, amylases produced by the fungus Aspergillus oryzae grown in rice koji hydrolyze starch to dextrin and glucose which is called saccharification. The Objective of this research was to understand the influences on amazake which brewed by varying temperature, pH and other factors that affecting the enzyme effects to qualities. This research design with 6 treatments brewed amazake incubated at 60oC, 75oC, 40oC which then sterilized, fourth treatment was incubated at 60oC without sterilized, fifth treatment was within lactic acid addition and sixth treatment, koji was substituted by enzyme agent. Parameter which observed was enzyme activity, sugar content and also organoleptic test that consist of 7 panelist. The parameters which include were sweetness, umami, sourness and aroma. From this research indicate that amazake product which incubated at 60oC have better quality than the others. Amazake which incubated at 60oC have better sweetness, good taste of umami, litlle sour and have good aroma.